PENGARUH GREEN MARKETING DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK ORIFLAME PURWAKARTA - Amna Mawardi (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
The Research aimed to determine factors that influencing the purchase decision of oriflame’s product. This research was take in two variables that affect the decision to purchase the green marketing (X1) and Product Quality (X2). Data collection using non-probability technique and the kind of the purposive sampling spread at les 100 respondents in Purwakarta that are active and ever of Oriflame’s consumer products. The research analyzed through the software SPSS 22. The outcome of this research, in partial such green marketing and the product quality have had a significant positive impact of the purchase decision. The whole dependent variable simultaneously influence of the purchase decision with F value count 55,587 and the economic situation of significant 0,000 < 0.05. R square value showed the results of 0,534 having meaning that whole of dependent variable influential simultaneously as many as 53,4 %.